Genetic diversity of Iranian populations of Pyrenophora graminea, the causal agent of leaf stripe disease on barley. Issue 7 (17th May 2022) - Dokhanchi, Haleh; Arzanlou, Mahdi; Abed‐Ashtiani, Farnaz
Abstract: Leaf stripe disease caused by Pyrenophora graminea is an economically significant disease of cultivated barley worldwide, including Iran. Considering economic impact of this disease on barley industry in Iran, in this study genetic diversity of P. graminea populations mainly collected from barley (229 isolates) in different regions of East Azerbaijan Province was examined using ISSR and RAPD molecular markers. The average polymorphic information content (PIC) values for ISSR and RAPD were 0.28 in both markers, and a significant correlation was observed between ISSR and RAPD data ( r  = .78, p  < .05). No clear clustering was found within P. graminea populations in relation to their geographical origins. Applying the unweighted pair group method with arithmetic mean (UPGMA) procedure and principal coordinates analysis (PCoA) revealed no obvious clustering of isolates based on geographic region. Totally, gene diversity of 0.2 was noticed among P. graminea isolates. High level of genetic differentiation (PhiPT = 0.257; p  ≤ .001), with 74% of the genetic variation occurring within populations and 26% occurring among populations, indicated the existence of population differentiation. In addition, a moderate amount of gene flow (Nm = 1.1985) was found between populations. Information obtained from this study may be beneficial to design and improve management strategies such as breeding resistant barley varieties to leaf stripe disease.